Development of (Gd, Ce) O2-impregnated (La, Sr) MnO3 anodes of high temperature solid oxide electrolysis cells - Chen, Kongfa; Ai, Na; Jiang, San Ping (The Electrochemical Society, Inc, 2010)
Gd0.2Ce0.8O1.9 (GDC)-impregnated La0.8Sr0.2MnO3 (LSM) electrodes are developed as the anodes for high temperature solid oxide electrolysis cells _SOECs_. The effect of anodic polarization current passage on the electrode behavior and microstructure of the LSM- and GDC-impregnated LSM anodes is investigated under low and high currents at 800°C. The results show that the electrocatalytic activity of the freshly prepared LSM is enhanced by the anodic polarization due to the reduction of LSM agglomerates and shrinkage of LSM particles under oxidation conditions at low polarization currents. However, high polarization current leads to the delamination at the interface, resulting in a significant increase in electrode polarization and ohmic resistances for the oxygen oxidation reaction. However, the impregnation of GDC nanoparticles not only enhances significantly the electrocatalytic activity for the oxygen oxidation reaction but also effectively inhibits the electrode delamination at the LSM anodeY2O3–ZrO2 electrolyte interface. The results demonstrate the promising potential of the GDC-impregnated LSM as effective anodes of high temperature SOECs.